-9.6+x=-13.5

Simple and best practice solution for -9.6+x=-13.5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9.6+x=-13.5 equation:


Simplifying
-9.6 + x = -13.5

Solving
-9.6 + x = -13.5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9.6' to each side of the equation.
-9.6 + 9.6 + x = -13.5 + 9.6

Combine like terms: -9.6 + 9.6 = 0.0
0.0 + x = -13.5 + 9.6
x = -13.5 + 9.6

Combine like terms: -13.5 + 9.6 = -3.9
x = -3.9

Simplifying
x = -3.9

See similar equations:

| 22-7m= | | 5(x-2)=5-2x | | x-5.5=8.6 | | 21a^5+211a^3b^2+10ab^4=0 | | 5(4x+2)=3(6x+3) | | 17*n=51 | | 4(2x-3)=2(5x+2) | | 36-n=15 | | 5x-2x-7x-3x=18+6-24-6 | | 4(4x+5)=6(6x-3) | | 12=g/4-3 | | y(70-20y+10)=0 | | y(70-2y+10)=0 | | (2+y)(3y-8)=0 | | y(70-2+y+10)=0 | | a*6+7=11 | | 39xn=3 | | x(70-10)=0 | | 3(5-3x)=25 | | 39/:n=3 | | 70-20+y+10=0 | | 18+-1n=10 | | -3(-3)+2(-3)-3=0 | | 34xn=34 | | 3[d+12]=8-4d | | 9(-9)-10(-9)+9=0 | | (9)9-10(9)+9=0 | | -5x+3=6x-2 | | 9+9=(5+4m) | | 39/n=3 | | x+(x*0.06)=50 | | x^3-x^2-32x+60=0 |

Equations solver categories